USING ACADEMAGOGY TO MEET THE NEEDS OF MILLENNIAL LEARNERS: A COMPARATIVE CASE STUDY - McAuliffe, Marisha; Winter, Abigail (European Scientific Journal, ESJ, 2014)
Higher education institutions across the world are experiencing a new generation of students, known as millennial learners. They are more technologically literate and digitally connected than previous generations of learners. To meet the teaching and learning needs of these learners, we must offer more deliberate and meaningful learning experiences and opportunities, where students can see the connections between new material and their own experiences and real world applications – an academagogic approach. This study compares the implementation of academagogy for two different groups of millennial learners – one a traditional face-to-face undergraduate Engineering unit, and the other a mixed-mode (online and face-to-face) undergraduate Design unit. The units are discussed in terms of their student evaluation results, both qualitative and quantitative, and in terms of their academic outcomes for students. Conclusions are drawn about the applicability of academagogy as a heuristic for improving teaching and learning across disciplines, as well as its strengths and limitations in terms of student results.